HOUSEHOLD RISK FACTORS FOR DIARRHOEA DISEASE IN CHILDREN UNDER FIVE YEARS OLD IN INDONESIA - Leni Pahmi; Wuryaningsih Caroline Endah (Faculty of Public Health, Sriwijaya University, 2019)
Background: Diarrhea caused the death of six children under five years old in the world in 2016, developing countries and low-income children under five under three years of age experienced diarrhea three times. Diarrhea is the main cause of underfive malnutrition, can be prevented and treated through safe drinking water and good sanitation. This study aims to find out the factors in the household that influence the incidence of diarrhea in children under five years old in Indonesia including drinking water sources, toilet facilities, maternal education and residence. Method: This study used a cross sectional design with Chi Square test, the data analyzed were secondary data from the results of the 2017 IDHS with a toddler population of 17,155, a sample of 2,440 diarrhea children under five years old and 14,715 children under five years old without diarrhea. Processing data using SPSS with univariate, bivariate, and multivariate analysis. Research Results: Chi Square Test results have a relationship between the incidence of diarrheal diseases and drinking water sources p-value = 0.035, toilet facilities p-value = 0,000, maternal education p-value = 0,000 and residence p-value = 0,000. Multivariate analysis with Logic Regression found that the most dominant factors affecting the incidence of diarrhea were toilet facilities, maternal education, and residence. Conclusion: The most dominant variables affecting the incidence of under-fives diarrhea are toilet facilities, mother's education and residence. Efforts by the government and the public to prevent diarrhea are to implement open defecation, hand washing with soap, management of household drinking water and food, safeguarding household waste, and securing household liquid waste.